Temporary Employment Agencies : A Route for Immigrants to Enter the Labour Market? - Pernilla Andersson; Eskil Wadensjö (Institute for the Study of Labor (IZA), 2004)
We study immigrants in temporary employment agencies in Sweden using a unique data set that covers all aged 16-64 who were employed by temporary employment agencies (TEAs) in Sweden in November 1999, with information on their employment status in 1998 and 2000. We find that young people, women, people living in big cities, and immigrants are overrepresented in the TEAs. Grouping immigrants after origin shows that immigrants from Africa, Asia and South America are greatly overrepresented in the sector. Immigrants are on average slightly older than the natives who work in TEAs, they are more often married, and women are less overrepresented among those born outside of Sweden. The immigrants are overrepresented among those with the lowest education and those with higher education. The mobility between employment status (employed in a TEA, other type of employment, unemployed, studying) differs between immigrants and natives in several respects. One result is that immigrants more often leave a TEA for another type of employment, which could be interpreted as employment in a TEA being used as a stepping stone to the labour market.
Keywords: J15; J61; J40; 330; immigrant workers; temporary agency work; contingent labour; temporary work; Leiharbeit; Arbeitsvermittlung; Migranten; Internationale Arbeitsmobilität; Berufliche Integration; Schweden